PTH-102 Preliminary Evidence for a Role of the Renin Angiotensin System in Intestinal Fibrosis in Crohn'S Disease Using Angiotensin Receptor Immunohistochemistry. (4th June 2013) - Ray, S; Soeda, J; Oben, J; Sanderson, J
Abstract : Introduction: Fibrosis is a major limitation to successful non-surgical treatment of Crohn's disease (CD) and is a cause of significant morbidity. The pathophysiological determinants of intestinal fibrosis in CD remain uncertain. The renin-angiotensin system (RAS) plays a critical role in blood pressure control and fluid and electrolyte homeostasis but has recently been implicated in fibrogenesis in multiple organ systems. Angiotensin II is the main active peptide in the RAS and evidence suggests it has important proliferative and profibrogenic roles acting through its AT1 receptor. Pharmacological blockade of the AT1 receptor has become a key element in the management of chronic cardiac and renal disorders and abrogates fibrosis. It also appears anti-fibrotic in chronic liver disease. Subsequent studies suggest that the AT2 receptor may act to oppose many of the proliferative and fibrogenic actions of AT1. Few studies have investigated a role for the RAS in intestinal fibrosis in CD. Aim: A preliminary study to use immunohistochemistry to determine AT1 and AT2 expression in resected ileum of patients with CD. Methods: Immunohistochemistry for AT1 and AT2 receptors was performed on archival formalin fixed paraffin embedded ileum of patients who had undergone resection for stricturing CD (n = 6), histologically normal ileum in patients undergoing colectomy for ulcerative colitis (UC) (n = 4) or right hemicolectomy for colon cancer (n = 1). We used commercial antibodies for AT1(SC1173) and AT2(SC9040) and the secondary antibody (Vector ImmPRESS Anti-Rabbit Ig (peroxidase) Polymer Detection Kit) under optimised conditions. Results: AT1 and AT2 staining patterns differed quite clearly between CD resection samples and those from UC and cancer controls. Control and UC cases showed clear staining of the muscularis for AT1 but consistently negative staining of epithelial or lamina propria compartments, whilst AT2 stained only the epithelial layer. Conversely, each of the 6 CD cases showed clear AT1 staining of the epithelial layer as well as muscularis but negative staining for AT2 in all areas. Occasional myofibroblast-like cells were also specifically stained by AT1. RTPCR analysis of RNA from CCD18CO cells (intestinal myofibroblast cell line) confirmed AT1 expression and no AT2 expression. Conclusion: These preliminary findings demonstrate a distinct difference in angiotensin receptor expression pattern in CD and non-CD ileum. This suggests a possible alteration in the balance between AT1 and AT2 receptor expression in CD strictures contributing to fibrogenesis and certainly merits further investigation Disclosure of Interest: None Declared.